1999
DOI: 10.1074/jbc.274.30.21011
|View full text |Cite
|
Sign up to set email alerts
|

Alternative, Non-secretase Processing of Alzheimer's β-Amyloid Precursor Protein during Apoptosis by Caspase-6 and -8

Abstract: Alzheimer's disease (AD) is a progressive neurodegenerative disorder. Although the pathogenesis of AD is unknown, it is widely accepted that AD is caused by extracellular accumulation of a neurotoxic peptide, known as A␤. Mutations in the ␤-amyloid precursor protein (APP), from which A␤ arises by proteolysis, are associated with some forms of familial AD (FAD) and result in increased A␤ production. Two other FAD genes, presenilin-1 and -2, have also been shown to regulate A␤ production; however, studies examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
96
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(101 citation statements)
references
References 44 publications
2
96
0
1
Order By: Relevance
“…However, it is also clear from our present work that caspase-cleaved APP per se is not a major contributor to A␤ generation, and therefore a scenario in which caspase-cleaved APP actively contributes to A␤ secretion remains unlikely. Thus, the possibility remains that cytotoxic effects derived from caspase cleavage of APP may result from the generation of new APP-derived C-terminal peptides (10,17,19) or C31, as we have proposed (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is also clear from our present work that caspase-cleaved APP per se is not a major contributor to A␤ generation, and therefore a scenario in which caspase-cleaved APP actively contributes to A␤ secretion remains unlikely. Thus, the possibility remains that cytotoxic effects derived from caspase cleavage of APP may result from the generation of new APP-derived C-terminal peptides (10,17,19) or C31, as we have proposed (12).…”
Section: Discussionmentioning
confidence: 99%
“…A number of laboratories have recently demonstrated that APP can be cleaved in the cytoplasmic domain by caspases after the aspartate residue at position 664, Val-Glu-Val-Asp 664 2Ala, (APP 695 numbering, or Asp 720 using APP 751 numbering) (7)(8)(9)(10)(11)(12). This cleavage would generate a C-terminal-truncated APP molecule that is ϳ3.5 kDa shorter (APP⌬C31) (7,12).…”
mentioning
confidence: 99%
“…14 Second, Casp6 activity in primary human neurons increases the production of Ab. 15,16 Although APP is a substrate of Casp6, [16][17][18] the caspasedependent increase of Ab is due to the cleavage of GGA3 (Golgi-associated, gamma adaptin ear containing, ARFbinding protein 3), an inhibitor of beta secretase. 19,20 Third, Casp6 cleaves valosin-containing protein resulting in the accumulation of cytosolic ubiquitinated misfolded proteins through an impairment of the ubiquitin-proteasomal system.…”
mentioning
confidence: 99%
“…Each of the four caspases, 3, 6, 7, and 8, have been shown to cleave APP in in vitro assays, and a major caspase site has been identified at Asp-720 (VEVD), resulting in the release of a fragment containing the last 31 amino-acids of APP (C31) and the production of APP⌬C31 (lacking Ala 721 to Asn 751 ) (5)(6)(7)(8). Two other major caspase sites have been recently identified at the N-terminal domain of APP Asp 197 and Asp 219 , leading to the production of a ϳ90 kDa fragment (APP⌬N).…”
mentioning
confidence: 99%